Antimicrobial resistance determinants and susceptibility profiles of pneumococcal isolates recovered in Trinidad and Tobago. (December 2017) - Hawkins, Paulina A.; Akpaka, Patrick E.; Nurse-Lucas, Michele; Gladstone, Rebecca; Bentley, Stephen D.; Breiman, Robert F.; McGee, Lesley; Swanston, William H.
Highlights: AWGS-based approach can accurately and reliably predict antimicrobial phenotypes. Observed rates of non-susceptibility to SXT and erythromycin were lower than reported for other countries in the region. In contrast, the proportion of β-lactam non-susceptibility was higher compared with other countries in the region. Multidrug resistance remains low but appears to be expanding clonally following introduction of pneumococcal vaccines. This clonal expansion is driven by the 19F-CC156 and 19A/F-CC236 lineages. Abstract: Objectives: In Latin America and the Caribbean, pneumococcal infections are estimated to account for 12 000–18 000 deaths, 327 000 pneumonia cases, 4000 meningitis cases and 1229 sepsis cases each year in children under five years old. Pneumococcal antimicrobial resistance has evolved into a worldwide health problem in the last few decades. This study aimed to determine the antimicrobial susceptibility profiles of pneumococcal isolates collected in Trinidad and Tobago and their associated genetic determinants. Methods: Whole-genome sequences were obtained from 98 pneumococcal isolates recovered at several regional hospitals, including 83 invasive and 15 non-invasive strains, recovered before ( n  = 25) and after ( n  = 73) introduction of pneumococcal conjugate vaccines (PCVs). A bioinformatics pipeline was used to identify core genomic and accessory elements conferring antimicrobial resistance phenotypes, including β-lactam non-susceptibility. Results and discussion: Forty-one isolates (41.8%) were predicted as resistant to at least one antimicrobial class, including 13 (13.3%) resistant to at least three classes. The most common serotypes associated with antimicrobial resistance were 23F ( n  = 10), 19F ( n  = 8), 6 B ( n  = 6) and 14 ( n  = 5). The most common serotypes associated with penicillin non-susceptibility were 19F ( n  = 7) and 14 ( n  = 5). Thirty-nine isolates (39.8%) were positive for PI-1 or PI-2 type pili: 30 (76.9%) were PI-1+, 4 (10.3%) were PI-2+ and 5 (12.8%) were positive for both PI-1 and PI-2. Of the 13 multidrug-resistant isolates, 10 belonged to globally distributed clones PMEN3 and PMEN14 and were isolated in the post-PCV period, suggesting clonal expansion.